2017
DOI: 10.1159/000479185
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Conditioning of Immune Responses with Cyclosporine A in a Murine Model of Experimental Autoimmune Uveitis

Abstract: Objective: We examined the role of behavioral conditioning of immune responses with cyclosporine A (CsA) on the development of Th1/Th17-driven experimental autoimmune uveoretinitis (EAU). Methods: Mice received a 0.2% w/v saccharin solution as conditioned stimulus combined with CsA (20 mg/kg) in 6 association trials at 72-h intervals. For evocation periods, conditioned mice were reexposed to saccharin, whereas the conditioned but not reexposed group received water only. Animals were immunized with human interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…As the inhibition of IL-2 secretion and proliferation is a central effector mechanism and is used as a pharmacodynamic measure of CsA, we used the IL-2 secretion and proliferation to measure the response to CsA in our study. Thereby, we confirmed the findings of our manuscript . Herein, systemic CsA treatment in EAU was associated with reduced proliferation and IL-2 secretion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As the inhibition of IL-2 secretion and proliferation is a central effector mechanism and is used as a pharmacodynamic measure of CsA, we used the IL-2 secretion and proliferation to measure the response to CsA in our study. Thereby, we confirmed the findings of our manuscript . Herein, systemic CsA treatment in EAU was associated with reduced proliferation and IL-2 secretion.…”
Section: Discussionsupporting
confidence: 91%
“…Thereby, we confirmed the findings of our manuscript. 35 Herein, systemic CsA treatment in EAU was associated with reduced proliferation and IL-2 secretion.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 92%
See 1 more Smart Citation
“…Even though results demonstrated that in comparison with rats taste-immune associative learning did not result in mice displayed reduced appetitive behavior(157). However, from the immunological perspective, learned immunosuppression was detectable reflected by a diminished production of IL-2(46,332).…”
mentioning
confidence: 84%
“…16 For instance, in classic studies with humans and rodents, cyclosporine A endowed gustatory CSs with conditioned, immunosuppressive qualities. 17,18 As more connections are found between ethanol and the immune system, it is important to analyze the mutual influence between neuroimmune signaling and ethanol-induced learning. Yet, to our knowledge, very few studies have assessed if immunomodulation induced by drugs of abuse can also be subject to conditioning.…”
Section: Impact Statementmentioning
confidence: 99%